Effect of Different Ecbolic Agents on Postpartum Reproductive Performance in Surti Buffaloes - Bhoi, Dhiren B.; Chaudhari, Naresh F.; Raval, Jitendra K.; Pandya, Gaurav M. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was conducted to evaluate the effect of different ecbolic therapies on puerperium in twenty four Surti buffaloes divided into four different groups consisting of six animals in each. Buffaloes in Group-I (T1) were not given any treatment and considered as control group. Group-II (T2) and Group- III (T3) buffaloes were injected methylergometrine (5 mg) and dinoprost tromethamine (25 mg) i/m, respectively, immediately after parturition. The animals in Group-IV (T4) received oral herbal ecbolic, 100 mL, daily for first 10 days postpartum. The time required for placental expulsion, persistence of lochial discharge, involution of uterus and service period were significantly (P<0.05) longer in T1 (14.86±6.65 h, 12.17±1.94 days, 36.50±4.76 days and 103.33±12.10 days, respectively) than T2 (10.33±2.71 h, 8.83±1.47 days, 33.33±3.61 days and 95.00±8.74 days), T3 (7.00±1.48 h, 8.00±1.41 days, 29.50±1.14 days and 86.50±4.88 days) and T4 (9.38±1.62 h, 10.17±1.47 days, 31.17±3.19 days and 97.80±7.21 days, respectively). The conception rates achieved in T1, T2, T3 and T4 groups/treatment were 50.00, 83.33, 100.0 and 83.33 %, respectively, with an overall conception rate of 79.17 % for all four groups of Surti buffaloes. The results were significantly superior with injection methylergometrine (5 mg) Group III given immediate postpartum, hence may be practiced to improve uterine health and postpartum fertility in buffaloes.